EAA Space Week – Lab for Exploring Teachers - Skiles, Jeffrey (Proceedings of the Wisconsin Space Conference, 2012)
Founded in 1953 in Milwaukee, WI, by a small group of enthusiastic aviators interested in building their own aircraft, the Experimental Aircraft Association (EAA) now brings together hundreds of thousands of people each year at the EAA AirVenture, the world’s largest aviation event. This international celebration recreates, on a grand scale, the atmosphere of challenge, anticipation, and accomplishment that inspired its founders. Over the decades, the organization’s mission has expanded to include other aircraft types including antiques, classics, warbirds, aerobatic aircraft, ultralights, helicopters, contemporary manufactured aircraft, and the continuing, expanding frontier of aerospace. AirVenture features educational workshops that promote personal achievement, hundreds of exhibitors who share state-of-the-art technology related to the science of flight, and a daily air show that celebrates the beauty and thrill of flight past, present, and future. Other EAA programs and resources include the EAA AirVenture Museum, the Young Eagles, SportAir Workshops, Timeless Voices, the Air Academy, Women Soar, and Space Week. These EAA programs are designed to serve all ages – from school-age children to adults – with an organizational effort to reach out to those demographic groups that are under-represented in aviation including women and minorities.